Feedbacks of Employers on Graduates of a State University’s External Campus in the Philippines - Juliet C. Lagrimas; Ronato S. Ballado; Yves Gerald E. Giray (Scientia Publica Media, 2025)
The study determined the feedback of employers on the work competence of graduates and crafted enhancement activities along the findings of the study. It was conducted at the University of Eastern Philippines, Laoang Campus. The study utilized a quantitative research design, particularly the descriptive design. Using purposive and quota sampling, it involved the immediate heads/supervisors of 150 graduates of the institution. To gather the needed data, a 20-item survey questionnaire was utilized. The data were subjected to statistical treatment using frequency counts and means. The study revealed that generally, the graduates were rated Very Satisfactory by the immediate heads/supervisors. The highest means of the graduates were on human relation skills, work ethics, and adequacy of knowledge in the work, while the lowest means were on leadership skills, entrepreneurship skills, and risk-taking skills. The Engineering graduates were rated Excellent, while Teacher Education, Criminology, and Industrial Technology graduates were rated Very Satisfactory. Graduates manifested Excellent ratings in human relation skills, work ethics, adequacy of knowledge in the field of work, capacity to learn new skills and procedures, ability to apply knowledge to the workplace, adaptability and flexibility, and teamwork. It is concluded that the graduates are doing well in their workplaces, although there are areas to improve in their workplace competence. The findings served as inputs for crafting curricular enhancement activities, particularly for the areas needing improvement.